Self-oscillation and period adding from resonant tunnelling diode-laser diode circuit - Figueiredo, J.; Romeira, B.; Slight, T.; Wang, L.; Wasige, E.; Ironside, Charlie (2008)
A hybrid optoelectronic integrated circuit comprising a laser diode driven by a resonant tunnelling diode can output various optical and electrical signal patterns that include self-sustained oscillations, subharmonic and harmonic locking and unlocked signals, with potential applications in optical communication systems. © 2008 The Institution of Engineering and Technology.